Bits of Gold: Women's Metaphors to Describe Havruta Study. Issue 3 (3rd July 2021) - Teomim-Ben Menachem, Esty; Livnat, Zohar
ABSTRACT: This study focuses on the metaphors used by modern Orthodox Israeli women aged 18-30 who studied in seminars in Israel where havruta learning is practiced to refer to their learning experience. It is assumed that these metaphors reflect the students' unmediated perception of havruta and highlight the significance of interpersonal relationships, sensitivity and accountability to the partner, the value of seeing a text from different viewpoints, and validation of one's experience. Moreover, the metaphors emphasize the interaction between the learners and the text and the learners' desire to be part of the dialogic interpretation process presented in the Talmudic text itself.